Currency Depreciation and Money Demand in Nigeria - Adeyemi, Oluwole J.; Oseni, Isiaq O.; Tella, S. A. (NIU Journal of Social Sciences, 2020)
Over the years, there has been controversy whether or not currency depreciation induces increased money demand. Previous studies appeared to have concentrated on the effects of currency depreciation on macroeconomic policy, while its relationship with money demand is scantly documented in the literature. This study therefore, explored this relationship and analyses the effects of currency depreciation on money demand in Nigeria. The study adopts ex-post facto research design and used secondary annual time series data from 1986 to 2017, obtained from Central Bank of Nigeria (CBN) Statistical Bulletin, 2017. The data collected were analysed using line graphs, Autoregressive Distributed Lag (ARDL) model with inferences drawn at 5% significance level. The results of trend and pattern of currency depreciation and money demand showed a pro-cyclical movement over the period of study relative to policies adopted by the government in the management of its currency exchange rate. Also, the results of the relationship between currency depreciation and money demand showed that currency depreciation (REXRD) (Î²=-0.003023, t=-0.245760) had negative and insignificant effect on money demand. Therefore, the study concluded that depreciation of the naira against other foreign currencies currency depreciation had no significant influence on changes in money demand in Nigeria over the study periods. It thus recommended that, government should create policies to enhance flow of credit to the real sector and sustained the stability of naira exchange rate. Keywords: Currency Depreciation, Money Demand, Macroeconomic policy, Exchange rate, ARDL.